(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper is an attempt to understand past and present of Shikarpur, one of historical city of Sindh. Besides geographical importance, this research evaluates historical analysis of causes of downfall and deteriorating conditions of the historical city, which was known as ‘Paris of Sindh’. This study also put light on different dynasty rule in the city. Moreover it highlights different majestic buildings and beauty of the city. This is purely qualitative research. In this research secondary data has been analyzed to support view point. Based on the arguments conclusion have been drawn.